Mundialización informativa, informacional y cultural - Aranha, Márcio Iório (2006)
The article deals with the remote and recent meaning of mundialization and the novelty that the concepts of informative, informational and cultural mundialization have introduced in the social investigation, mainly as opposed to the technological innovation of the telecommunications and the cultural interferences derived. The central reference of the article is in the treatment of the thinking society as world-wide society recognized from the concepts of informative, informational and cultural mundialization, and in the understanding of the system-world economics also like a cultural organization.